2013
DOI: 10.1590/s0103-65132013005000049
|View full text |Cite
|
Sign up to set email alerts
|

Método para desenvolvimento de práticas de gestão integrada em clusters industriais

Abstract: O objetivo deste artigo é propor um método para que as empresas pertencentes a clusters industriais desenvolvam coletivamente, por meio de ações guiadas pela governança, práticas integradas introdutórias de gestão da qualidade, meio ambiente e segurança e saúde do trabalho. Esse método foi desenvolvido com base em uma consistente revisão teórica e em uma pesquisa de campo no cluster metal-mecânico de Sertãozinho-SP, realizada para familiarizar os pesquisadores com o ambiente de estudo e identificar boas prátic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…The footwear, metallurgical, and construction industries are sectors with high rates of work accidents (Zhou et al, 2015) and have been the subject of OHS management studies in Brazil (Oliveira et al, 2010;Vitoreli et al, 2012;Almeida & Nunes, 2014;Nadae et al, 2013;Gomes et al, 2016). The studied enterprises have an average of 28 employees.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The footwear, metallurgical, and construction industries are sectors with high rates of work accidents (Zhou et al, 2015) and have been the subject of OHS management studies in Brazil (Oliveira et al, 2010;Vitoreli et al, 2012;Almeida & Nunes, 2014;Nadae et al, 2013;Gomes et al, 2016). The studied enterprises have an average of 28 employees.…”
Section: Resultsmentioning
confidence: 99%
“…In the metallurgical industry, the support of senior management and the human resource department, and the active participation of employees are decisive; the main difficulties in this management originate from communication failures and lack of OHS indicators and strategic vision for safety (Oliveira et al, 2010). The main impediments for OHSMS implementation are lack of a consistent policies of support for companies, effective participation of other stakeholders, effective cooperation among entrepreneurs, and concern about OHS (Nadae et al, 2013), in addition to lack of experience with management systems, limited number of employees and insufficient financial resources (Vitoreli et al, 2012).…”
Section: Ohsms In Small Enterprisesmentioning
confidence: 99%
“…Proposition 2 (P2): Organizational culture influences the implementation of IMS. Finally, based on the literature review we identify two moderate variables are the type of industry and firm size suggested by Karapetrovic & Casadesús (2009), Casadesús et al (2007) and Nadae & Oliveira (2010) that can impact both the IMS and the TBL performance, suggesting the following propositions:…”
Section: Proposed Framework Discussionmentioning
confidence: 96%
“…A visão integrada dos fatores que predispõem ao adoecimento, assim como as ações de prevenção e eliminação destes, é importante para que a empresa tenha uma produtividade adequada sem colocar em risco a segurança e saúde dos seus colaboradores (Nadae et al, 2014).…”
Section: Introductionunclassified